2015
DOI: 10.3109/10717544.2015.1122676
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of S-nitrosoglutathione-alginate for prolonged delivery of nitric oxide in intestines

Abstract: S-nitrosothiols are a class of NO-donors currently under investigation for the treatment of various diseases. In this study, we developed a novel NO-donor (S-nitrosoglutathione-alginate, SNA) by cross-linking alginate with S-nitrosothiols, which can deliver NO in a sustained manner. This compound can be further evaluated for oral delivery to treat Crohn's disease. This new compound was prepared using a two-step procedure involving (I) linkage of reduced glutathione to alginate and (II) post-nitrosation with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In in vivo experiments, LPS-challenged rats showed a drop in serum NO, and significant rise in creatinine and BUN, which were successfully countered with GSNO treatment (179). The therapeutic potential of GSNO is yet to be established with the application of new GSNO nanocarriers (180,181) or administration methods suitable for oral applications as target drugs (182).…”
Section: •−mentioning
confidence: 99%
“…In in vivo experiments, LPS-challenged rats showed a drop in serum NO, and significant rise in creatinine and BUN, which were successfully countered with GSNO treatment (179). The therapeutic potential of GSNO is yet to be established with the application of new GSNO nanocarriers (180,181) or administration methods suitable for oral applications as target drugs (182).…”
Section: •−mentioning
confidence: 99%
“…Two compounds were synthesized with NO loading 174 ± 21 μmol/g and 468 ± 23 μmol/g respectively. An ex vivo permeation study showed that these compounds can exhibit a sustained release for at least 10 h [44] Encapsulation of RSNO in polymeric nanoparticles also provides a promising strategy in sustaining NO release from RSNO. Eudragit ® RL was used to prepare GSNO-loaded nanoparticles (GSNO-NP).…”
Section: Resultsmentioning
confidence: 99%
“…GSNO has been shown to promote the S -nitrosation of catalase, which modulates its activity in processes like growth, development and response to stress in plants ( Corpas et al, 2019 ) and animals ( Tyther et al, 2007 ), and GSNO-directed inhibition of catalase by S -nitrosation has been linked to obesity in humans ( Palma et al, 2020 ). Moreover, S -nitrosothiols such as GSNO have been used for many years as cardiovascular therapeutics and are currently under investigation as treatments for other diseases, including Crohn’s disease ( Shah et al, 2016 ). There, the ability of GSNO to regulate and modulate the actions of signaling cascades by post-translational modifications like S -nitrosation could account for its efficacy as a therapeutic for a variety of conditions.…”
Section: Discussionmentioning
confidence: 99%